GIANT ADRENAL SCHWANNOMA PRESENTING AS ADRENAL INCIDENTALOMA WITH MALIGNANT FEATURES - Young, Louisse Lynn Antoinette; Elises, Jose Carlo; Bejar, Ralph; Mirhan, Clarisse Veronica (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Adrenal schwannomas, which are benign nerve sheathtumors, are rare causes of incidentaloma, accounting for 0.7% of adrenal tumors. A 42-year-old Filipino male presented with right flank pain. An ultrasound showed an incidental right suprarenal complex mass. CT scan of the adrenals showed an 11.1 x 11.1 x 11.5 cm heterogenous, predominantly cystic right suprarenal mass with progressive enhancement, compressing the liver, right kidney, and inferior vena cava, with unenhanced attenuation of 32 Hounsfield units, and an absolute percentage washout of -87%, implying possible malignancy. Plasma-free metanephrines, aldosterone, renin, serum cortisol after 1mg DST, and DHEAS were all unremarkable. He underwent an open right adrenalectomy for an impression of non-functioning adrenocortical carcinoma. Final histopathology diagnosis revealed spindle cell neoplasm and immunohistochemistry staining with S100 showed strong, diffuse, nuclear staining observed in neoplastic cells, compatible with a schwannoma. To our knowledge, this is the first reported case of a giant adrenal schwannoma in the Philippines.